Learned Value Shapes Responses to Objects in Frontal and Ventral Stream Networks in Macaque Monkeys. (10th May 2016) - Kaskan, Peter M.; Costa, Vincent D.; Eaton, Hana P.; Zemskova, Julie A.; Mitz, Andrew R.; Leopold, David A.; Ungerleider, Leslie G.; Murray, Elisabeth A.
Abstract: We have an incomplete picture of how the brain links object representations to reward value, and how this information is stored and later retrieved. The orbitofrontal cortex (OFC), medial frontal cortex (MFC), and ventrolateral prefrontal cortex (VLPFC), together with the amygdala, are thought to play key roles in these processes. There is an apparent discrepancy, however, regarding frontal areas thought to encode value in macaque monkeys versus humans. To address this issue, we used fMRI in macaque monkeys to localize brain areas encoding recently learned image values. Each week, monkeys learned to associate images of novel objects with a high or low probability of water reward. Areas responding to the value of recently learned reward-predictive images included MFC area 10 m/32, VLPFC area 12, and inferior temporal visual cortex (IT). The amygdala and OFC, each thought to be involved in value encoding, showed little such effect. Instead, these 2 areas primarily responded to visual stimulation and reward receipt, respectively. Strong image value encoding in monkey MFC compared with OFC is surprising, but agrees with results from human imaging studies. Our findings demonstrate the importance of VLPFC, MFC, and IT in representing the values of recently learned visual images.